A broad‐range yeast expression system reveals Arxula adeninivorans expressing a fungal self‐sufficient cytochrome P450 monooxygenase as an excellent whole‐cell biocatalyst. Issue 4 (5th March 2014) - Theron, Chrispian W.; Labuschagné, Michel; Gudiminchi, Ramakrishna; Albertyn, Jacobus; Smit, Martha S.
Abstract The feasibility of using a single vector to clone a cytochrome P450 monooxygenase (P450) in different yeasts and then compare whole‐cell hydroxylase activity was investigated. A broad‐range yeast expression vector using the ylTEFp to drive expression of the cloned gene and the scTEFp to drive the hygromycin resistance marker gene was used to clone the genes encoding two self‐sufficient P450s, CYP102A1 and CYP505A1. Both genes were cloned into Saccharomyces cerevisiae, Kluyveromyces marxianus, Yarrowia lipolytica (two strains) and Arxula adeninivorans. 4‐Hexylbenzoic acid (HBA), which is subterminally hydroxylated by both CYP102A1 and CYP505A1, was used to compare whole‐cell hydroxylase activity of transformants. Kluyveromyces marxianus and A. adeninivorans exhibited activity with both CYP102A1 and CYP505A1, while S. cerevisiae only displayed CYP102A1 activity and Y. lipolytica only CYP505A1 activity. The highest CYP102A1 activity (0.8 mM HBA converted in 24 h) was observed with concentrated resting‐cell suspensions of S. cerevisiae. The CYP505A1 activity observed with growing cultures of A. adeninivorans was however at least 12 times higher than the CYP102A1 activity of S. cerevisiae with up to 2 mM HBA converted within 6 h. The use of K. marxianus and A. adeninivorans for P450 expression has not previously been reported.